Effect of experimental sample size on local Weibull assessment of cleavage fracture for steel. Issue 7 (23rd December 2016) - Zhang, Z; Qian, X
Abstract: This paper examines the sample size of the experimental datasets in calibrating the Weibull parameters for the modified three‐parameter Weibull stress framework, so as to enhance the experimental strategy for cleavage assessment of ferritic steels based on a local approach. The present work generates a large number of random and independent subsets from the 'Euro steel' fracture toughness database for the calibration procedure. The calibration of the Weibull parameters utilizes a subset of high‐constraint specimens and a subset of low‐constraint specimens from the Euro steel database to resolve the uniqueness issue in the calibration procedure reported in previous studies. This investigation reveals strong dependence of the calibrated Weibull modulus on both the constraint differences between the high‐constraint subset and the low‐constraint subset and the size of the selected subsets. The scale fracture toughness value, however, does not exhibit significant dependence on the constraint difference between the two subsets of specimens. The confidence level of the scale fracture toughness, nevertheless, still exhibits strong dependence on the sample size of the experimental data.